A theoretical study on e--CO elastic collision using the configuration interaction method to describe the target - Martins, Maria das Graças Reis (2005)
It is presented a theoretical study on electron -CO collisions in the (5-20) eV energy range. Specifically, elastic differential cross sections (DCS) are calculated using the configuration interaction (CI) method to describe the target. Static and exchange contributions to the interaction potential are obtained exactly from a CI wave function with single and double excitations. The DCS are obtained using the Schwinger variational iterative method (SVIM). It is observed that the discrepancies between Hartree-Fock and CI results are more significant for low energies and small angles.